Application Of Skinner's Behaviorist Learning Theory In Learning Arabic Speaking Proficiency/ Penerapan Teori Belajar Behavioristik Skinner Dalam Pembelajaran Maharah Kalam - Addaeroby, Muhammad Fahdin; Febriani, Erma (Bumi Lingua Edu Center, 2024)
Skinner's behaviorist theory is a behavior change caused by the interaction between stimulus and response. This theory views learning as a change in student behavior. The purpose of this study is to describe B.F. Skinner's behaviorist theory, its implementation in Arabic speaking skill/ Maharah Kalam learning, and the problems in its application. The research method used is a literature study with a qualitative approach. Research results 1. Behaviorist learning theory is a behavior change caused by the interaction between stimulus and response. This theory views learning as a change in student behavior. 2. Implementing behaviorism for Maharah Kalam learning includes introducing and creating a conducive environment, using supporting learning media, and providing reinforcement as a positive response to student behavior. Applying Skinner's behaviorist theory has proven effective in Maharah Kalam's learning, especially in creating a supportive learning environment and providing positive reinforcement. 3. The problems in its application include internal factors, such as intelligence, which influences their ability to adapt to the environment when learning Arabic, especially in learning to communicate in that language.